Attitudes and behaviors that differentiate clergy with positive mental health from those with burnout. Issue 1 (2nd January 2020) - Case, Andrew D.; Keyes, Corey L. M.; Huffman, Katie F.; Sittser, Kelli; Wallace, Amanda; Khatiwoda, Prasana; Parnell, Heather E.; Proeschold-Bell, Rae Jean
Abstract: Clergy provide significant support to their congregants, sometimes at a cost to their mental health. Identifying the factors that enable clergy to flourish in the face of such occupational stressors can inform prevention and intervention efforts to support their well-being. In particular, more research is needed on positive mental health and not only mental health problems. We conducted interviews with 52 clergy to understand the behaviors and attitudes associated with positive mental health in this population. Our consensual grounded theory analytic approach yielded five factors that appear to distinguish clergy with better versus worse mental health. They were: (1) being intentional about health; (2) a "participating in God's work" orientation to ministry; (3) boundary-setting; (4) lack of boundaries; and (5) ongoing stressors. These findings point to concrete steps that can be taken by clergy and those who care about them to promote their well-being.